(3cJGH aj GdefWbs
(3ChdgG (B:s
(3ef eSeGg GddGRe dg PgfkG ai MjK cPdc cOdGdI GdEfSGf Ydi bGHd GdYde hUfYI GdcJGHI s
(3BNQgG (B:s
(3hEf cGfJ eG fYI Ndb cGf GdMGd Ydi YcS dLhGR ELJeGYgG hYdjc HJaUjM GdCeKdI hGddg CYde HGdUhGH Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdeLGejYs